Method for Calculating the Sound Absorption Coefficient for a Variable Range of Incidence Angles - Sergio Alfio YORI (Archives of Acoustics)
The theoretical estimation of sound absorption coefficient of a surface may give very different results. This will depend on the type of sound field assumed in the theoretical model used for the estimation of its sound absorption coefficient. Absorption coefficients for normal and diffuse sound fields are widely known, although they may be far from the absorption values given by an absorbing material when it is finally installed inside a room or enclosed space, where a sound field closer to a spherical wavefront is more likely to be found. This work presents a theoretical study, which is addressed at obtaining a mathematical expression to calculate the sound absorption coefficient for a variable range of incidence angles, called $α_s$. The presented method uses a circular sound field incidence as an approximation to a spherical incidence. The estimation of this coefficient $α_s$ is based on obtaining the incident and reflected sound fields for a surface located facing a lineal source. The advantage of this calculation method over others lies on its capability to give results for circular, normal and random wave incidence depending on the range of incidence angles considered in the calculation.